Difficulties and challenges in the implementation of resuscitation training in Germany based on surveys from the Heart Saver Project in Brandenburg - Izabela Jastrzebska; Konrad Bohm; Philipp Humbsch; Robert Gintrowicz (International Journal of First Aid Education)
Background:In Germany, survival rates for out-of-hospital cardiac arrest (OHCA) are low, with only 10.4% of patients surviving after 30 days, compared to 14% in Norway. Layperson resuscitation is a key factor, with 85% of Norwegian OHCA cases involving bystander intervention, while in Germany, the rate is only 51%, resulting in 2,200 preventable deaths each year. Despite recommendations since 2014 to introduce resuscitation training in schools, implementation has been limited. By 2022, only two federal states—Mecklenburg-Western Pomerania and Baden-Württemberg—had fully adopted these lessons, and participation in pilot projects, such as one in Brandenburg, has been inconsistent. Methods:A descriptive survey study was conducted to understand the barriers to implementing resuscitation lessons in schools. First, all 33 schools involved in the Brandenburg pilot project were surveyed, identifying 5 that participated and 28 that did not. Follow-up interviews were conducted with teachers from 12 of the 28 non-participating schools. The survey asked about preferences for internal versus external trainers, willingness to implement lessons in the future, and perceived usefulness of the program. Additionally, web-based research was conducted to assess the status of resuscitation education across Germany’s federal states, focusing on curriculum integration, design guidelines, and cost coverage. Results:Most teachers found resuscitation lessons valuable but reported significant barriers such as insufficient training, lack of time, and inadequate materials. Schools preferred using their own staff rather than external specialists. Web research revealed that, while some states have included resuscitation training in their curricula, most only have pilot projects or lack a formal plan. Funding for teaching materials and continuous training remains limited. Conclusions:Although the importance of resuscitation training is well recognized, widespread implementation in Germany faces significant challenges. The COVID-19 pandemic further delayed progress, exposing weaknesses in infrastructure. To improve OHCA survival rates, a comprehensive plan with sufficient funding is necessary to support teacher training, provide materials, and ensure long-term support. Expanding resuscitation training could potentially save thousands of lives each year.